2007
DOI: 10.7748/ns2007.01.21.18.35.c6398
|View full text |Cite
|
Sign up to set email alerts
|

A review of the merits of the nurse practitioner role

Abstract: Over the past two decades, nurses have begun to undertake tasks and assume responsibilities traditionally associated with medicine. This has led to debate, particularly with regard to the extension of the nurse prescribing role. This article examines some of the key issues surrounding the advancement of nursing practice and the effect on the nursing and medical professions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Research has demonstrated that ENPs are able to care for low acuity patients within the emergency department (Sakr et al, 1999;Barr et al, 2000;Wilson and Bunnell, 2007;Wilson and Shifaza, 2008). However, there has never been a standardised, validated approach in the assignment of presumed low acuity patients to ENPs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research has demonstrated that ENPs are able to care for low acuity patients within the emergency department (Sakr et al, 1999;Barr et al, 2000;Wilson and Bunnell, 2007;Wilson and Shifaza, 2008). However, there has never been a standardised, validated approach in the assignment of presumed low acuity patients to ENPs.…”
Section: Discussionmentioning
confidence: 98%
“…However, each nurse and department has designed the ENP's interference slightly different. There is a lack of consensus about role boundaries, titles, clinical accountability and educational requirements (Griffin and Melby, 2006;Fisher et al, 2006;Wilson and Bunnell, 2007). In an attempt to clarify ENP role boundaries and, at the same time, manage patient streaming, the MCH developed a stream system to the MTS, to identify patients suitable for treatment by ENPs (van der Linden et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse prescribing has also been described as ‘a contentious issue that produces a good deal of conflict and anxiety (Schober and Affara 2006, 37).’ Nurses have assumed prescribing responsibilities for an extended period without legal recognition (Keeling 2004; Wilson and Bunnell 2007). Nurses expressed concern for adequate preparation and training to prescribe and were uneasy with the increasing responsibility (Latter and Courtenay 2004; Lewis‐Evans and Jester 2004).…”
Section: Praxismentioning
confidence: 99%
“…Nurses expressed concern for adequate preparation and training to prescribe and were uneasy with the increasing responsibility (Latter and Courtenay 2004; Lewis‐Evans and Jester 2004). Difficulties have been identified with the limited number of products available in the formulary for nurse prescribing (Wilson and Bunnell 2007).…”
Section: Praxismentioning
confidence: 99%
“…This has resulted in a variety of differing job titles which impacts upon workforce planning to meet the needs of OOH services. Therefore, clarifying nursing roles is important to recognise the value and professional capability of nurses, and ensure there is consistent understanding of what each role entails linked to education, regulation and maintaining professional competence (Wilson & Bunnell ). In addition, without role clarity, it is difficult to measure the effectiveness and efficiency of service provision (Lowe et al .…”
Section: Introductionmentioning
confidence: 99%